Redefining translation and interpretation in cultural evolution - Seel, Olaf Immanuel, 1967- (Information Science Reference, 2018)
"This book provides relevant theoretical framework and the latest empirical research findings in the area of culture-related translation research in the context of cultural evolution. It provides insights and support to all other researchers, professionals and trainees concerned with culture and communication, e.g. cultural studies, cultural management, communication science, sociolinguistics, pragmalinguistics"--